Pemanfaatan Situs Candi Agung Amuntai Sebagai Sumber Belajar Sejarah di MAN 2 Hulu Sungai Utara - Mardiani, Fitri; Fahriannor, Fahriannor; Subiyakto, Bambang (Lambung Mangkurat University, 2022)
Utilization of historical learning resources that are close to the surrounding environment can help teachers explore the material being taught to students to be more real. Often considered monotonous with the lecture method, learning history can now be explored more deeply with direct learning activities outside of school. Archaeological remains such as the site of the Agung Amuntai Temple is one of the relics of the Hindu kingdom in the city of Amuntai, South Kalimantan. Its existence can be used by teachers as a source of learning history for students at MAN 2 Hulu Sungai Utara. The research method used is descriptive qualitative which takes pictures of student learning activities at MAN 2 Hulu Sungai Utara which utilizes the Agung Temple site as a source of learning history. Data collection techniques through observation, interviews, and documentation during the implementation of learning in class X MIA 4, data analysis through data reduction, data presentation, and drawing conclusions. The data validity technique uses technique and source triangulation. Utilization of the Agung Amuntai Temple site as a source of learning history provides real experience to students in learning history and can hone sensitivity to the surrounding environment. so, it can be directed to love, maintain and care for historical heritage objects that are around because of the requirements for the noble cultural values of the Indonesian nation.